Analysis of a didactic sequence in a study on Ichthyology through playfulness and active methodologies based on the BNCC and the CTES approach (Research, Society and Development, 2021)
For teachers, who have recently been working remotely or with hybrid teaching, the didactic sequence comes with an support tool. The didactic sequence (DS) is not a replacement for lesson plans, as these are mandatory, but it helps the teacher in organizing and meeting the objectives of their classes. Thus, in this work, a didactic sequence for the teaching of science was developed, more precisely in Ichthyology, and its analysis was made based on the CTSA approach and the BNCC, established for the Early Years of Elementary School. Initially, this sequence was made to be applied in Science Teaching, within the context of an Aquaponics Project that would be developed at the Nossa Senhora do Sagrado Coração Support Center (CANSCC) in Itajubá-MG, with emphasis on vertebrates and ichthyology. This DS was developed in 2020, associated with the Semeando Cientistas Project at the Federal University of Itajubá (UNIFEI) with a subsidy from the Pro-Rectory of Extension (PROEX-UNIFEI). It is expected from this didactic sequence, due to the BNCC, that the application of active methodologies, such as stories and games, as well as resources such as dance and the use of playfulness, tends to help positively in the teaching-learning process of Science. The CTES approach, in the didactic sequence, results in the civic education of critical individuals, capable of promoting a sustainable action to preserve the environment, in a harmonious society, which respects values and differences.